Bibliometric research on analysis of links between periodontitis and cardiovascular diseases - Tang, Kuangyun; Wu, Yongjia; Zheng, Qianhan; Chen, Xuepeng (Frontiers in Cardiovascular Medicine, 2023)
Background: Periodontitis (PD) and cardiovascular diseases (CVD) rank among the most prevalent pathologies worldwide, and their correlation has been a subject of prolonged investigation. Numerous studies suggest shared etiological factors; however, a definitive causal connection remains unestablished. The objective of this study was to employ bibliometric and visual analyses in order to comprehensively examine the overarching characteristics, focal areas of research, and prospective trends pertaining to the PD-CVD relationship.